A TECHNICAL REVIEW ON SMART CONTRACT PLATFORMS, LANGUAGES AND APPLICATIONS IN BLOCKCHAIN - Gopal Krishan Prajapat; Shekhawat Pradeep; Dharmendra Yadav (Proceedings on Engineering Sciences)
Blockchain is the technology which greatly attracted the industries as well as the academics of the educational system because of its variety of applications and innovations around the globe. Smart contract is one of the most highly used technological move in the blockchain technology which increased its attention among the researchers. A smart contract has been embedded in the blockchain as an agreement that does not need any third-party intervention and executes automatically to perform different sophisticated tasks. Significant research has been done in the area of smart contract in blockchain in recent years. The smart contract has its impact in many industrial applications like supply chain management, digital identity, IOT, business processes etc. This paper aims to review the recent work that has been done in the area of smart contracts in different domains. We will present a comparative study of smart contract platforms, languages and applications under different categories like security, management, social application needs, etc.